The Meaning of Sincerity in Transformational Leadership at The Islamic Boarding School Educational Institution - Rahmatika, Nuniek (Universitas Ahmad Dahlan, 2024)
Sincerity is defined as hope only in Allah SWT. A leader can find the meaning of his members' sincerity so that they have better work enthusiasm. The purpose of this research is to determine transformational leadership behavior that interprets the sincerity of its members and the form of meaning of sincerity in transformational leadership that can realize innovation in Islamic boarding school educational institutions. This research approach uses phenomenology. Data collection used triangulation methods, namely observation and interviews. Data validity techniques are carried out using triangulation methods, member checking, and auditing. The results of this research found that the meaning of Ikhlas in transformational leadership is that sincerity is analogous to the spirit while charity is the body so that Ikhlas can create a conducive climate and can develop creativity and innovation in Islamic boarding school educational institutions.